Identifikasi Keunikan Lansekap Kampung Loloan di Jembrana - UTAMI, NI WAYAN FEBRIANA; KOHDRATA, NANIEK (Jurnal Arsitektur Lansekap; Vol.2, No.1, April 2016, 2016)
ABSTRACT Identification on Distinctive Landscape of Kampong Loloan in Jembrana Most of landscape in Bali is closely related to Hindu’s culture. In contrary, it is different in Kampong Loloan which is an area located in the Ijogading riverbank in Negara District, Jembrana Regency, Bali Province. It is unique because of the people and the culture, more and less, are identically similar to Malay culture. Their ancestors are mostly Malay or Bugis people or other ethnicities. The objective of this study was to identify the biophysical and social characteristic of Kampong Loloan along with spatial distribution of cultural and historical site found on the area. The methods used was conducted with three phase, 1) data collection with ground thruth check and literature study; 2) data analysis of biophysical and social character with spatial analysis; and 3) synthesis of cultural characteristics. The results showed that land use patterns in Kampong Loloan was based on river ecological zone. Three zone were identify, 1) the upstream zone (Ketugtug and Pertukangan sub-village); 2) the midstream zone (Loloan Timur and Kerobokan sub-village), and 3) the downstream zone (Mertasari and Terusan sub-village). The tangible heritage found in Loloan was stilt houses (rumah panggung) but the existence was threatened. Moreover, Malay-Loloan language, Adrah musical art, and Bugis martial art were found as the intangible heritage. Map analysis showed that cultural and historical site in Kampong Loloan were mostly found in the east side of Ijogading riverbank. Keywords: cultural landscape, Ijogading riverbank, Loloan, vernacular landscape